85/5000 THE TERRITORY IN CONTEMPORANEITY (THE RECOVERY OF TERRITORIAL POLICIES) (Revista LIDER, 2020)
Territory, understood as a localized society with territorial identity, is being reevaluated in the context of globalisation and any fear that it might pass on to a discreet second plane, is completely unfounded. The author supports this thesis supplying elements stemming from Anthrolopology, Sociology, Psychology, Economy, Geography, Political Science and Urban Planning, all of which speak of a territory of increasing importance for the generation of current development, understood and related to associativity, knowledge, potentiating the human being to the human person, sustainability, ethics and endogeneity.